The Students’ Reading Comprehension of Narrative Text At The Second Grade Of SMP Negeri 6 Kota Jambi In Academic year 2018/2019 - Nuryani Nuryani; Suyadi Suyadi (Universitas Batanghari Jambi, 2020)
Many students find some problem in reading. A major problem faced by the students in reading texts is that they often do not comprehend the overall have been major obstacles to understanding. Narrrative text is a text, shich related a serried of logically and chronologically related event that are cause or experienced by factor, there are generic structure, orientation, complication, resolution, reorientation or coda. The research is aimed at knowing how to the students’ reading comprehension focused at narrative text in the second grade of SMP Negeri 6 Kota Jambi in Academic year 2018/2019. The research was conducted in a pre-experimental method. The subject of the research class VIII J, this class consists of 36 students. This research, the data were collected from tests result. The tests consisted of pre-test and post-test, the instrument in this study was a test of students reading in narrative texts and answer the questions about narrative stories, The test was in the form of multiple choice test with five alternative answer a,b,c,d,e with 20 test. The finding of research was the mean score of pre-test is 40, and the mean score of post-test is 61,8. each test to find out the improvements of students’ reading comprehension in narrative texts. The result of the research shows that the comparison of Frequency Scores Pre-Test and Post-Test, the persentage of the students who got the score low category in the pre-test (94,4%) and in post-test score high category (71,8%). It can be seen that in mastering narrative texts that can significantly improve students' reading comprehension skills.Key word : Reading Comprehension, Narrative Text.